P6_4 Tee Off Into Space - Levin, Guy; Eddison, Jacob; Marsden, Joe; Vigneswara, Darshan (Physics Special Topics, 2017)
Our aim in this paper was explore the possibility of hitting a gold ball into orbit around various objects in the solar system by using the orbital velocity equation. We found this to be possible around four moons, four dwarf planet candidates and a trojan of Jupiter with masses greater than 10^18kg.